THE EFFECT OF THE USE OF AUDIO VISUAL MEDIA ON STUDENT LEARNING OUTCOMES IN CLASS X IPA VIRUSES IN SENIOR HIGH SCHOOL - Ira Susanti; Zahri Zahri (Sensei International Journal of Education and Linguistic, 2021)
This study aims to determine the learning outcomes of students who are taught using audio-visual media in the biology subject of virus material at SMA Negeri 1 Meureubo, West Aceh Regency and to find out how students respond during learning using audio-visual media. This study used a randomized research design, subject to posttest only control group, where the research was a quasi experimental design. The experimental class was taught using audio-visual learning while the control class was taught using conventional methods without using audio-visual media. The results of this study indicate that the control class obtained an average value of learning outcomes of 71.750. Whereas in the experimental class, the average value of learning outcomes was 78.833. Thus the average value of student learning outcomes in the experimental group was higher than the average value of student learning outcomes in the control group. Data analysis using t-test obtained the value of t count> t table, namely 2.319> 1.713 with a significance of 0.05. The conclusion of this study is that there is a significant influence on student learning outcomes between the average learning outcomes of students using audio-visual media and the average learning outcomes of students who do not use audio-visual media in the learning process of grade X IPA students at SMA Negeri 1 Meureubo Regency. West Aceh.